Wachholz, a new exquisite dinosaur-bearing fossiliferous site from the Upper Triassic of southern Brazil. (August 2015) - Müller, Rodrigo Temp; da Rosa, Átila Augusto Stock; Roberto da Silva, Lúcio; Aires, Alex Sandro Schiller; Pacheco, Cristian Pereira; Pavanatto, Ane Elise Branco; Dias-da-Silva, Sérgio
Abstract: The present contribution reports a new fossiliferous site from the Caturrita Formation (Upper Triassic of Paraná Basin, Southern Brazil), which yields articulate, complete, associated, and exceptionally well-preserved dinosaur specimens, together with the sole occurrence of an isolated tooth ascribed to a carnivore indetermined archosauriform. These specimens increase the sauropodomorph record from this geological unit. A preliminary evaluation of such specimens suggests that sauropodomorph dinosaurs could have been more abundant in Norian Faunas from southern Brazil, considering the increased sampling here reported. So far, about six specimens are previously recognized (disregarding Guaibasaurus ) from the Caturrita Formation, and here we add four specimens, or even five if consider an additional autopodium. Also, the morphology of the isolated carnivorous-type tooth differs from other described carnivorous archosauriform teeth from the Caturrita Formation. Hence, it might represent a still undescribed taxon. Further studies of these specimens will certainly provide new data regarding biostratigraphy, phylogeny, paleoecology, and taphonomy, as this new fossiliferous locality preserves one of the most representative dinosaur records from the Norian worldwide. Highlights: We describe a new dinosaur-bearing fossiliferous site from the Caturrita Formation. It yielded complete and exceptionally well-preserved dinosaurs. This is remarkable due to the worldwide scarcity of complete early Norian dinosaurs. The new site comprises at least four sauropodomorphs. In addition, a new taxonomic record is proposed based on an archosauriform tooth.